If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -4x = 11x Solving 5 + -4x = 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 5 + -4x + -11x = 11x + -11x Combine like terms: -4x + -11x = -15x 5 + -15x = 11x + -11x Combine like terms: 11x + -11x = 0 5 + -15x = 0 Add '-5' to each side of the equation. 5 + -5 + -15x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -15x = 0 + -5 -15x = 0 + -5 Combine like terms: 0 + -5 = -5 -15x = -5 Divide each side by '-15'. x = 0.3333333333 Simplifying x = 0.3333333333
| 5-(6-3n)=2 | | G(x)=x^2+3x-54 | | 12x/4=-2y/2 | | G(x)=x^2+9x+20 | | 2=x/-5 | | 9b-9b=11(b-7)+8(b+12) | | 2y^2+18y+80=0 | | -4/7en-3/7en= | | -8=1x+-12-10 | | (3x-4)(7x+4)=0 | | x^2=36-5x | | 4x-5+2(3x)+17=-2-3x+(9-5) | | 13-x=-1 | | -4/7en--3/7en= | | Y=27x+10.50 | | 4(3y-1)=-40 | | 7x-2(x-4)= | | 10x+5+8=12x-3x+80 | | V+5v=42 | | 6.5k=-240 | | 26+x+3+4=90 | | 4x-3+2(3x)+17=-2-2x+(16-6) | | 2x-80=53+9x | | 81x^3=256x | | -3/5•8/6 | | (1+u)(2u+3)=0 | | f(x)=3x^4-4x^3 | | 60+21.50+21.50=124.50 | | n+124=436 | | 4x=10i | | log(9x+5)=4 | | -16t^2+72t-81=h |